Incidence of multiple births in relation to current regulations in Turkey regarding embryo transfer - Semra Kahraman; Ipek Nur Balin Duzguner; Soner Duzguner; Yucel Sahin; Cihat Sen (BMC, 2021)
Abstract Background Before 2010, there were no regulations in Turkey regarding the number of embryos to be transferred in one cycle. In March 2010, regulations restricting this number were implemented by the Turkish Ministry of Health. These specify the transfer of a maximum of one embryo in the first and second cycles and a maximum of two embryos in subsequent cycles in women aged < 35, and a maximum of two embryos in women aged ≥35 in any one cycle. Our study evaluates the effect of these regulations. Methods This large retrospective single center study first evaluates the incidence of multiple pregnancies before and after the implementation of the 2010 regulations. Secondly, it compares the clinical outcomes of double blastocyst transfer (DBT) and single blastocyst transfer (SBT) performed in compliance with these regulations from 2014 onwards. Results After the introduction of the 2010 regulations, the multiple pregnancy rate decreased significantly from 37.9 to 15.7%. The singleton live birth rate increased significantly, whereas multıiple live birth rates significantly decreased (p = < 0.001). When the clinical outcomes of SBT and DBT performed in compliance with regulations from 2014 onwards were evaluated, in patients < 35 years, the multiple pregnancy rate decreased from 47.2% in the DBT group to 1.7% in the SBT group (p = < 0.001). In patients ≥35 years, in the DBT group, the twin birth rate was again high at 28.4%, whereas in the SBT group, it was only 1.8% (p = < 0.001). Importantly, there was no statistically significant difference in clinical pregnancy rates between these two groups. Conclusion Turkish regulations have led to an encouragement of double embryo transfer (DET) as a routine practice, with many patients understanding it as an absolute right to have two embryos transferred. The results of our study suggest that, especially in the light of the success of blastocyst transfer, the Turkish regulations should be amended to limit the use of DET and encourage the use of single embryo transfer except in exceptional cases and particularly in women under 35 years old.